The relation between radiographic manifestation and clinical characteristics of congenital radioulnar synostosis in children: A retrospective study from multiple centers - Hong, Pan; Tan, Wei; Zhou, Wei-Zheng; Zheng, Yu; Li, Jin; Zheng, PengFei; Tang, Xin (Frontiers in Pediatrics, 2023)
Objective: To review the radiographic manifestation and clinical appearance of children with congenital radioulnar synostosis (CRUS) retrospectively. Study design: Retrospective cohort study of children with CRUS from multiple medical centers. Results: A total of 329 patients (male 259, female 70) with an average age of 5.4 years (0.5 - 16 years old), were included in this study. In particular, 145 patients (145/329, 44.1%) demonstrated bilateral involvement, and 184 patients (left 123, right 61) demonstrated unilateral involvement. As for Clear and Omery (C&O) classification, most patients belonged to Type III, and then followed by Type IV. As for Chinese Multi-center Pediatric Orthopedic Study Group (CMPOS) classification, most patients belonged to Type III, and then followed by Type II and Type I. In C&O Type III, 92.03% patients demonstrated severe pronation. According to CMPOS classification, 92.98% Type I patients demonstrated neutral to mild pronation, 72.17% Type II patients demonstrated moderate pronation, and 92.03% Type III patients demonstrated severe pronation. Conclusion: Although CRUS is a rare forearm deformity, there are certain relation between radiographic manifestation and clinical forearm functional restriction. CRUS patients of C&O or CMPOS Type III classification might suffer severe pronation deformity and warrant early intervention.